BIMBINGAN BELAJAR SUKARELA BAGI SISWA KURANG MAMPU DI DESA SELUANG KELURAHAN MAYASOPA - Dyulius Thomas Bilo; Vinsensia Nitamawar Tafonao (Jurnal PKM Setiadharma, 2023)
Tutoring is an effort to help students (students) in completing their education well. Tutoring is not always obtained only from schools, but the guidance they need to get from families and the environment in which they live. Tutoring is needed, especially by children still in elementary school, because that is the golden age where they experience rapid moral, language, cognitive, artistic, and physical motor development. Tutoring aims to guide, educate, and motivate students (students) in carrying out their responsibilities and obligations at school, for example, mastering well the lessons given at school and doing homework. The method used in conducting a tutoring program is through lectures and discussions. This tutoring follows the lessons of students (students) in school so that when they face the test, they have understood the lesson. The continuation of this program for three months has given progress to children who are enthusiastic about participating in it.